The Use of Interferon Inducers in an Infectious Disease Clinic - A. A. Shuldyakov; E. P. Lyapina; L. A. Soboleva; M. G. Romantsov; T. A. Perminova; V. I. Kuznetsov; L. S. Narkaitis (Антибиотики и Химиотерапия)
The article presents the scientific substantiation of the use of interferon inducers in an infectious disease clinic the inducers of endogenous interferon of various chemical groups with antiviral action are examined and analyzed. The authors describe specific features of interferon induction by different drugs. They evaluate the effectiveness of cycloferon in the complex treatment of patients with influenza and other acute respiratory viral diseases, herpesvirus, arbovirus and intestinal infections, tuberculosis, including in the presence of HIV infection, chronic brucellosis, etc.